Unilateral Partial Aphalangia and Hemimelia in an Adult Dog and Cat: Clinical Presentation and Radiography Findings - Abu-Seida, AM (Journal of the Hellenic Veterinary Medical Society, 2023)
Congenital digital deformities are uncommon anomalies in dogs and cats and many of them are still not recorded in veterinary literature. This report describes the clinical presentation and radiological findings in a 3-year-old male German shepherd dog with a right pelvic limb partial aphalangia and an 11-year-old female Persian cat with a left thoracic limb partial hemimelia. The dog showed an absence of the fourth digit of right pes with abnormal footpads and a wide interdigital space between the third and fifth digits. Radiography revealed presence of all metatarsals, absence of the middle and distal phalanges of the fourth digit, under development of the proximal phalanx and foot pad of the fourth digit as well as fusion between the foot pads of fourth and fifth digits. The cat had only one digit, two nails and one rudimentary foot pad in the left thoracic limb. The left thoracic limb was shorter than the contralateral limb. Radiography revealed short ulna, presence of three carpal bones, absence of all metacarpals and presence of one digit with three phalanges. No other congenital disorders were noted in both animals. No treatment was offered because the dog and cat were coping well with their defects. In conclusion, dogs and cats with unilateral partial aphalangia and hemimelia can survive into adulthood with a reasonable quality of life, particularly indoor animals. Radiography plays a crucial role in complete description, classification and definite diagnosis of these defects in companion animals.